PENGARUH BOLA STANDAR DAN BOLA MODIFIKASI TERHADAP KEMAMPUAN PASSING ATAS DALAM PERMAINAN BOLAVOLI PADA MURID SD INPRES TANGKALA II MAKASSAR - Ali Muhaimin (Universitas Pendidikan Mandalika, 2016)
This study aims to determine; (1) To determine the extent of the effect of standard ball size number 4 on the ability of passing on to the elementary school students Inpres Tangkala II Makassar. (2) To determine the extent of the effect of modifications to the ball passing ability on the elementary school students Inpres Tangkala II Makassar. (3) To find out which is better effect between standard ball ball size number 4 with modifications to the ability of passing on to the elementary school students Tangkala II Makassar.Jenis this study is the kind of experimental research. The population is all elementary school students Inpres Tangkala II with a sample of 30 people. Further divided into two groups with ordinal matching technique is to group standard 15 ball and 15 ball modification. Sampling technique is technique saturated samples. Data analysis technique used is the paired t-test and unpaired t-test. Based on the results of this study concluded that (1) a significant difference using a standard ball against passing ability on elementary school students Inpres Tangkala II Makassar City thitung 12.854 and ttabel obtained a value of 2.045 (0.000 <α0.05); (2) a significant difference using a modification to the ball passing ability on elementary school students Inpres Tangkala II of Makassar tcount = 27 798 and table =2,045 while the significant value gained 0,000 <α 0.05. Due to significant levels of less than0.05 α (3) the use of a modified ball better improve significantly the passing on of the use of standard ball at the elementary school students Inpres Tangkala II Makassar City t = 3,358 and the value table = 2,045, while the value of significant obtained 0.002 <α 0:05, because the significance value smaller than α 0:05.